A gradient poly(vinyl alcohol)/polysaccharides composite film towards robust and fast stimuli-responsive actuators by interface co-precipitation. Issue 40 (5th October 2021) - Huang, Bai; Zhu, Ge; Wang, Shuzhan; Li, Qunyang; Viguié, Jérémie; He, Hui; Dufresne, Alain
Abstract : The fabricated films have excellent mechanical properties and can quickly perform predictable complex deformation to simulate blooming states of flowers. Abstract : Polymer actuators with fast stimulus responsiveness and programmable deformation have received continuous attention in the fields of biomedicine, intelligent biosensors, and soft robotics. More stringent requirements are now demanded on biocompatibility, controllable deformation and mechanical properties of the actuator. In this study, a simple interface co-precipitation strategy is proposed for the preparation of polymer/polysaccharide composite actuators. The co-precipitation process is induced at the interface of the polyvinyl alcohol (PVA)/chitosan (CS) solution and cellulose nanofibril (CNF) suspension, thereby obtaining a gradient distribution of the different components and physical cross-linking points. The prepared composite films exhibit rapid large deformation actuating behavior in response to water and deformation recovery in salt solution, as well as excellent tensile strength (63.6 ± 6.9 MPa) and toughness (26.9 ± 4.5 MJ m −3 ). In addition, CNF alignment caused by shrinkage endows the films with predictable complex three-dimensional deformability. The different spatial transformations of actuators are demonstrated, such as a bionic flower imitating a Confederate Jasmine bent along the long axis. This simple interface co-precipitation method provides significant guidance for the preparation and application of polymer actuators based on polysaccharides.